2022
DOI: 10.3390/biology11101434
|View full text |Cite
|
Sign up to set email alerts
|

The First Survival Score for Patients Aged ≥80 Years Irradiated for Brain Metastases

Abstract: Survival scores facilitate personalized cancer treatment. Due to demographic changes, very elderly patients are more prevalent than in the past. A score was developed in 94 patients aged ≥80 years undergoing whole-brain radiotherapy for brain metastases. Dose fractionation, treatment period, age, sex, performance score (ECOG-PS), tumor type, count of lesions, metastases outside the brain, and interval tumor diagnosis to radiotherapy were retrospectively evaluated. Independent predictors of survival were used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The preferred radiotherapy regimens were similar for different age groups including elderly (65+) and very elderly (80+) patients. However, in order to provide the appropriate treatment for these patient groups, age-specific survival scores should be used for both bone and brain metastases (4)(5)(6)(7)(8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preferred radiotherapy regimens were similar for different age groups including elderly (65+) and very elderly (80+) patients. However, in order to provide the appropriate treatment for these patient groups, age-specific survival scores should be used for both bone and brain metastases (4)(5)(6)(7)(8).…”
Section: Resultsmentioning
confidence: 99%
“…In general, elderly and very elderly patients should not be treated with other radiotherapy regimens than patients aged <65 years. However, for optimal treatment personalization, age-specific survival scores should be used for both elderly and very elderly patients with bone or brain metastases (4)(5)(6)(7)(8). Several specific survival scores for these patient groups were developed within the Interreg-Project TreaT (5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…The longest observed survival was 6.1 months in octogenarians managed with BSC. Given that survival after WBRT was disappointing ( 13 , 14 ), more efficacious, yet function-preserving SRS (or fractionated variants) should be considered, if KPS is ≥70 and active treatment is needed. Median survival in the literature was around 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Rades et al. reported a retrospective analysis of WBRT, the historical standard approach that is less commonly employed now, in 94 octogenarian patients ( 13 ). Their median survival was 2.0 months and the authors proposed a survival score featuring three prognostic groups based on Eastern Cooperative Oncology Group (ECOG) performance status (PS), number of lesions (single versus multiple), and extracranial metastases (present versus absent).…”
Section: Common Treatment Optionsmentioning
confidence: 99%
“…It is therefore relevant to perform separate analyses, which inform decisionmaking and result in optimized selection criteria for brain-directed radiotherapy. In addition to already validated survival prediction models, such as recursive partitioning analysis (RPA) classes, diagnosis-specific graded prognostic assessment (DS-GPA) and LabBM score (9)(10)(11)(12), which all can be recommended for clinical implementation, Rades et al suggested a new model that was derived from a dedicated study of irradiated patients aged ≥80 years (13). Their score was developed in 94 patients undergoing WBRT.…”
mentioning
confidence: 99%